The strategic role of human resource management on competitiveness of smes, and perceptions of entrepreneurs on human resource management - Uyar, Arzu (My University, 2013)
KOBİLERİN REKABET GÜCÜNÜN ARTMASINDA İNSAN KAYNAKLARI YÖNETİMİNİN STRATEJİK ROLÜ, VE GİRİŞİMCİLERİN İNSAN KAYNAKARI YÖNETİMİNE BAKIŞ AÇILARI Bu çalışmanın amacı, Türkiye’nin ekonomik büyümesine büyük etkisi olan Küçük ve Orta Büyüklükteki İşletmeler’in sürdürülebilirliği için İnsan Kaynakları Yönetimi’nin stratejik önemini ortaya koymaktır. Belirtilen evren 420 kişidir ve tümüne ulaşılması güç olduğundan örneklem grubunu Küçük ve Orta Ölçekli İşletmeleri Geliştirme ve Destekleme İdaresi Başkanliği (KOSGEB) tarafından desteklenen, “Yeni Girişmci Desteği” Programına katılan Ege bölgesindeki 85 girişimci oluşturmaktadır. Bunun için, KOBİ’lerin kurulması ve gelişmesini sağlayan 85 girişimcinin 3 bölümden ve toplamda kapalı uçlu 31 sorudan oluşan anket yoluyla İnsan Kaynakları Yönetimi’ne bakış açıları (yaklaşımları) incelenmiştir. Elde edilen veriler SPSS Statistics 17.0 analiz edilmiştir. İlk olarak, ankete katılanların 10 demografik özellik ve İnsan Kaynakları Fonksiyonları temelinde hazırlanan 20 soru için ayrı ayrı dağılımları incelenmiştir. 11. soru ise girişimci olmak için motivasyon faktörlerini ölçmüştür. Çapraz tablo analizi ile 10 demografik özellik ve 20 soru tablolarda çıkan yüzdelere göre yorumlanmıştır. Son olaraksa, uygulanan anketteki her bir demografik özellik ile 20 soru arasında istatistiksel bir ilişki olup olmadığı Ki-kare testi (x2 test) ile incelenmiştir. Buna göre, demografik verilerle ilişkili/ ilişkisiz olan İnsan Kaynakları Fonksiyonları ortaya konmuştur.

ABSTARCT THE STRATEGIC ROLE OF HUMAN RESOURCE MANAGEMENT ON COMPETITIVENESS OF SMEs, AND PERCEPTIONS OF ENTREPRENEURS ON HUMAN RESOURCE MANAGEMENT This thesis seeks to state the strategic role of Human Resource Management on competitiveness of SMEs which have great impacts on the development of Turkish economy.Due to the fact it is very time consuming and expensive to observe the population as 420 entrepreneurs, the sample of the research is 85 entrepreneurs who attended “The Support for New Entrepreneur” Program in Aegean Region supported by Small and Medium Enterprises Development Organization (KOSGEB). In order to examine the perceptions of 85 entrepreneurs who are the founders and developers of SMEs, a questionnairewith3 sections and close-ended 31 questions was conducted. The Statistical Package for the Social Sciences (SPSS) version 17.0 was used to analyze the data. Firstly,the distribution of entrepreneurs for 10 demographical characteristics and 20 questions were examined separately. By question 11, the factors that encouraged each of the start-up business owners for being an entrepreneur were analyzed. 10 demographical characteristics of the respondents and 20 questions were interpreted by Cross-Tabulation according to the percentages in the tables. Finally, the Chi-square test (x2 test) in a Contingency tables was used to determine whether there is a statistical relationship between between demographic variables and 20 questions.
Keywords: Ekonomik Durum; Girişimcilik; Kamu Yönetimi; Personel Yönetimi; Rekabet; Türkiye